In situ measurement of bulk modulus and yield response of glassy thin films via confined layer compression. Issue 6 (30th March 2020) - Brazil, Owen; de Silva, Johann P.; Chowdhury, Mithun; Yoon, Heedong; McKenna, Gregory B.; Oliver, Warren C.; Kilpatrick, Jason; Pethica, John B.; Cross, Graham L.W.
Abstract: Abstract : The measurement of thin film mechanical properties free from substrate influence remains one of the outstanding challenges in nanomechanics. Here, a technique based on indentation of a supported film with a flat punch whose diameter is many times the initial film thickness is introduced. This geometry generates a state of confined uniaxial strain for material beneath the punch, allowing direct access to intrinsic stress versus strain response. For simple elastic–plastic materials, this enables material parameters such as elastic modulus, bulk modulus, Poisson's ratio, and yield stress to be simultaneously determined from a single loading curve. The phenomenon of confined plastic yield has not been previously observed in thin films or homogeneous materials, which we demonstrate here for 170 -470 nm thick polystyrene (PS), polymethyl-methacrylate (PMMA) and amorphous Selenium films on silicon. As well as performing full elastic -plastic parameter extraction for these materials at room temperature, we used the technique to study the variation of yield stress in PS to temperatures above the nominal glass transition of 100 °C.